Pollution, Exposure and Risk of Biogenic Amines in Canned Sea Fish: Classification of Analytical Methods Based on Carbon Spheres QuEChERS Extraction Combined with HPLC - Xinying Guo; Zhiying Dai; Weibing Zhang (Molecules, 2022)
This study investigated the pollution characteristics, exposure levels and health risk assessments of seven kinds of biogenic amines (BAs) in eight varieties of canned sea fish products (n = 131) on the Chinese market. Carbon spheres QuEChERS mixed dispersion solid phase extraction combined with HPLC was used for the classification and analysis of batch samples. The average recovery of single BAs obtained by this method is 92.3~97.7%, and the relative standard deviation is 1.9~4.8%. Different varieties of samples have different degrees of pollution, the mass concentration of single BAs range 0.45~27.74 mg/kg, and the total concentration of ΣBAs range 18.77~368.50 mg/kg, of which the concentration of Σ4BAs range 11.53~368.50 mg/kg. The composition of four BAs is mainly putrescine, cadaverine, histamine and tyramine, which always play an important role in the exposure level and risk assessment of samples. The exposure level of BAs in the human body ranges 67.03~209.52 μg∙kg−1∙d−1. The health risk assessment shows that the gender trend of exposure risk level of BAs is male > female (young age), female > male (middle and old age), the age trend is young age > old age > middle age, and the regional trend is city > countryside. The food safety index of BAs in samples is 0.0062~0.0195, which is far less than 1, so the risk is within the controllable range.